Професор Л.М. Славін у польській археології - Ґурба, Я.С. (Археологія, 2007)
У замітці розглянуто співпрацю професора Л.М. Славіна з польськими колегами в 1940—1960-х рр. До сих пор одной из малоизученных сторон многогранной деятельности профессора Л.М. Славина является его участие в налаживании международного научного сотрудничества Института археологии АН УРСР в 1940—1960-х гг. Об этом свидетельствуют, к примеру, творческие контакты Л.М. Славина с польскими археологами, принимавшими участие в раскопках Ольвии и проходившими под его патронатом научную стажировку на кафедре археологии Киевского государственного университета им. Т.Г. Шевченко. Until now one of the little-known aspects of the many-sided work of Professor L.M. Slavin was establishment of international scientific cooperation of the Institute of Archaeology of AS of Ukraine, during 1940—1960s. Among the specific examples of this are the long-term professional relations of L.M. Slavin with Polish archaeologists participating in excavations of Olbia and doing study tours at the archaeology department of Kyiv University.